2015
DOI: 10.1152/jn.00693.2014
|View full text |Cite
|
Sign up to set email alerts
|

Different pools of glutamate receptors mediate sensitivity to ambient glutamate in the cochlear nucleus

Abstract: Yang Y, Xu-Friedman MA. Different pools of glutamate receptors mediate sensitivity to ambient glutamate in the cochlear nucleus. J Neurophysiol 113: 3634 -3645, 2015. First published April 8, 2015 doi:10.1152/jn.00693.2014.-Ambient glutamate plays an important role in pathological conditions, such as stroke, but its role during normal activity is not clear. In addition, it is not clear how ambient glutamate acts on glutamate receptors with varying affinities or subcellular localizations. To address this, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…To test this, we used the irreversible, activity-dependent NMDAR antagonist MK-801 to assess the level of ambient synaptic glutamate-induced activation of synaptic NMDARs, and whether this level differs between excitatory and inhibitory neurons. We first recorded NMDAR EPSCs (−60 mV, 0.5 mM Mg 2+ ) to establish a baseline response, and paused stimulation while voltage-clamping the postsynaptic neurons at +40 mV in the presence of MK-801 (20 μM) to block synaptic NMDARs activated by ambient glutamate 25 , 59 . After 5 min, the holding potential was switched back to −60 mV with synaptic stimulation resumed.…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we used the irreversible, activity-dependent NMDAR antagonist MK-801 to assess the level of ambient synaptic glutamate-induced activation of synaptic NMDARs, and whether this level differs between excitatory and inhibitory neurons. We first recorded NMDAR EPSCs (−60 mV, 0.5 mM Mg 2+ ) to establish a baseline response, and paused stimulation while voltage-clamping the postsynaptic neurons at +40 mV in the presence of MK-801 (20 μM) to block synaptic NMDARs activated by ambient glutamate 25 , 59 . After 5 min, the holding potential was switched back to −60 mV with synaptic stimulation resumed.…”
Section: Resultsmentioning
confidence: 99%
“…The idea of RMP modulation by endogenous ACh has also been proposed for fusiform and cartwheel cells of the DCN ( Godfrey et al, 1998 ). It has also been shown that the SBC RMP is set by endogenous glutamate through mGluRs ( Chanda and Xu-Friedman, 2011 ; Yang and Xu-Friedman, 2015 ). Although we could represent the muscarinic effect only in a simplified form in the model, some general conclusions can be drawn from our in silico experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SBCs are often seen as a simple relay. However, a number of studies have shown that SBC activity is not only affected by the excitatory ANF input: the resting membrane potential and action potential probability of SBCs are under the influence of slow inhibitory synaptic inputs ( Kuenzel et al, 2011, 2015 ; Nerlich et al, 2014a ; Keine and Rübsamen, 2015 ) and metabotropic glutamate receptors ( Chanda and Xu-Friedman, 2011 ; Yang and Xu-Friedman, 2015 ). Additionally, SBC activity is influenced by GABA B receptors ( Chanda and Xu-Friedman, 2010 ) and the dynamics of voltage-activated conductance ( Cao et al, 2007 ; Oertel et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the strong voltagedependent magnesium block of most NMDARs limits their ability to pass a physiologically relevant tonic current (Vicini et al, 1998). Despite this, tonic activation of NMDARs has been shown to influence excitability in a variety of neuronal subtypes across multiple brain regions (Sah et al, 1989;Chergui et al, 1993;Moos et al, 1997;Dalby and Mody, 2003;Le Meur et al, 2007;Povysheva and Johnson, 2012), including at times when the target neurons are not artificially depolarized (Yang and Xu-Friedman, 2015;Riebe et al, 2016). Based on their unique properties, including high glutamate affinity and low-magnesium affinity, GluN2C/DRs have been hypothesized to be the primary mediators of a glutamatergic tonic current (Le Meur et al, 2007;Riebe et al, 2016).…”
Section: In Sensitivity To Ambient Glutamatementioning
confidence: 99%